An overview of the technology and design of base isolated buildings in high seismic regions in the United States - Wiles, Jessica Irene (Kansas State University, 2008)
Seismic hazards are a primary concern in some of the most populous regions in the United States. Performance-based seismic design has brought about new technology advances and introduced an innovative approach towards constructing seismic resistant buildings. Base isolation and structural damping systems are becoming increasingly utilized methods of advanced seismic resistance. This relatively new design approach presents various issues that must be addressed throughout the design and construction processes. A brief background on the origin, dynamics, and hazards of earthquakes and a discussion on designs of traditional, fixedbased structures is presented in this report. A description for selected types of new advanced seismic restraint systems, with an emphasis on base isolation, is also provided. Examples of current applications of buildings equipped with base isolation are presented. This report concludes with a review of the fundamental design methodology for structural base isolation along with additional requirements not addressed by the current building codes.
Keywords: Base isolation; Structural engineering; Seismic structural design; Engineering, Civil (0543)